Socio-Economic Conditions of Women in the Slum of Kumbalagodu Industrial Area of Bangalore Region - Manoj S; Rajith Kumar H B; M Shubhangini M (Al-Makki Publisher, 2022)
In Karnataka, Migration has played an important role in accelerating urban growth by attracting rural migrants to urban areas for economic reasons despite a lack of physical infrastructure in terms of housing, drinking water supply, drainage, sanitation, and other amenities. As a result, the migrant rural poor are forced to seek for unofficial alternatives, leading in the growth of slums and squatter communities. Slums are now a regular sight in practically all of India's major cities. As a result of the constant influx of rural migrants, the quality of life diminishes, and the gap between demand and availability of basic services and other infrastructure in the areas deepens. This present research article is to study and examine slum areas and their living conditions, and finding out the most critical and problematic zone of the slums. In relation to this article, the objectives is to assess the socio-economic conditions of women dwellers of slum in Kumbalagodu industrial area and to suggest appropriate measures to advance the standard of living conditions of women in slum of the Kumbalagodu industrial area of Bangalore region and it also suggests suitable measures for upliftment of women of slum of case study area.